Man On the Run - Weber, Carl 1964- (New York : Grand Central Publishing, 2017)
"It was the night before his wedding, fifteen years ago, that the nightmare began for Jay Crawford--locked up for a crime he never committed. Now he's escaped prison and wants nothing more than to clear his name and protect his family. To get justice, he'll need the help of the three best friends who have always had his back--Wil, Kyle, and Allan. But a man on the run requires absolute trust--and Jay may just be setting himself up for the ultimate betrayal"--
Keywords: Escaped prisoners -- Fiction; Fugitives from justice -- Fiction; False imprisonment -- Fiction; Male friendship -- Fiction; FICTION / African American / Contemporary Women; FICTION / African American / General; FICTION / Contemporary Women; FICTION / African American / Urban Life; FICTION / Urban Life; Urban fiction; Thrillers (Fiction)